(untitled) (KYAMC Journal, 2022)
Background: Birth trauma usually occurs, particularly in long and difficult labour or fetal mal presentations. Although with advancements in technology and improved obstetric care and liberal use of cesarean section deliveries, serious birth trauma is decreasing worldwide. Appraisement of common triggers of birth trauma is the key ingredient for provision of high quality prenatal & perinatal care to reduce the incidence and severity of birth trauma. Objective: To evaluate the risk factors of birth trauma. Materials and Methods: This case control study was carried out in the department of Neonatology, Dhaka Medical College Hospital from 14th August, 2018 to 14th February, 2019. Total 100 newborns were enrolled in the study. Among them 50 were cases, diagnosed as birth injury & 50 were controlls without birth injury. Results: Most common birth injury encountered, was caput succedaneum15 (30%). The next common injuries were cephalohematoma was 11(22%) & subgalealhemorrhage 11 22%). Other injuries were skin & soft tissue injury in 5 (10%), followed by sternomastoidhemorrhage, accidental cut injury, clavicular fracture, humerus fracture, facial nerve palsy, erbs palsy, subconjunctival Haemorrhage. The predisposing factors for mechanical birth trauma were primiparity (P = 0.005), advanced maternal age (28.99 ± 5.4)> (26.5 ± 4.5) (p value =0.01), mal presentation (P = 0.05), oxytocin use (P < 0.01), Prolonged labor (P < 0.01), large size of the baby (p=0.046), VD(p=0.004). Conclusion: The study concluded that the commonest birth injury was caput succedaeneum and primiparity, advanced maternal age, prolonged labor, large-sized baby, mal presentation were the significant risk factors for birth injury. KYAMC Journal Vol. 13, No. 03, October 2022: 129-133